PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI BAGIAN PENDAFTARAN RAWAT JALAN RSIA SETYA BHAKTI DEPOK - Syaikhul Wahab; Septia Farensa (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to determine the quality of service on patient satisfaction in the outpatient registration department of RSIA Setya Bhakti Depok. The research method used is quantitative research with a descriptive approach. While the data collection technique used was a non-probability sampling technique with a sample of 91 outpatient registration visitors at RSIA Setya Bhakti. The indicators in this study were tested using validity and reliability tests. The results of this study indicate that the Quality of Service, namely Direct Evidence (47.3%), Reliability (51.6%), Responsibility (51.6%), Assurance (52.7%), Simultaneously and partially have an effect on satisfaction patients namely Harmonious Relations (46.2%), Repurchase (48.4%), Loyalty (51.6%), Word Of Mouth (47.3%) through data processing the results obtained there is an influence between the variable quality of service to variable Outpatient satisfaction at RSIA Setya Bhakti Depok was 96.2% and the remaining 3.8% was influenced by other variables. Keywords : Quality of Service. Consumer Satisfaction